Efektivitas Penggunaan Model Pembelajaran Generatif dengan Alat Peraga Puzzle pada Materi Teorema Pythagoras terhadap Kemampuan Pemecahan Masalah Matematis - Noor Halipah; Mayang Gadih Ranti (UIN K.H. Abdurrahman Wahid Pekalongan, 2023)
This research aims to determine students' mathematical problem solving abilities in learning using a generative learning model (Generative Learning) with puzzle props using Pythagorean theorem material in class VIII MTsN 11 Tabalong. This type of field research with experimental methods and a quantitative descriptive research approach is used to collect data using tests, namely problem-solving ability tests which have been tested for validity by expert validators. The sampling technique is purposive sampling, namely classes VIII B and VIII C. Data collection techniques include: test methods, documentation and interviews. The research results show: (1) The mathematical problem solving abilities of students in the experimental class with a class average score of 73.38 are in the good category. (2) The students' mathematical problem solving abilities in the control class with a class average score of 63.19 are in the sufficient category (3) There is a significant difference between students' mathematical problem solving abilities in learning with and without using generative learning models. ) with puzzle teaching aids on Pythagorean theorem material in class VIII MTsN 11 Tabalong.